Long-term impact of COVID-19 on cardiovascular health of healthcare workers of a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2023)
Background: The coronavirus disease (COVID-19) is a multisystem disease that sometimes affects the cardiovascular system (CVS) during acute illness and follows a protracted course in a proportion of patients causing ‘post-COVID syndrome’. Exercise tolerance test (ETT) can assess functional capacity and imaging modalities like echocardiography and cardiac magnetic resonance (CMR) can assess structural and functional status of cardiovascular system (CVS) efficiently. However, the pattern of cardiovascular involvement and its effect on functional capacity in COVID-19 survivors long after the index illness are inadequately known. This study was carried out to detect the functional status and imaging findings in COVID-19 recovered healthcare workers.Methods: This cohort study was carried out in the Department of Cardiology of the National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from July 2021 to December 2021. Thirty male healthcare workers, previously not known to have any cardiac disease, who suffered from reverse transcriptase polymerase chain reaction (RT-PCR)-confirmed COVID-19 of mild severity at least 3 months back were included. Besides clinical evaluation, ETT, echocardiography and CMR were done.Results: The mean age was 37.2±4.7 years. The mean time interval from RT-PCR positivity was 317.4±85.7 days. The functional capacity was good in the study subjects; the achieved metabolic equivalents (METs) were 13.0±1.5. The mean left ventricular ejection fraction (LVEF) was 66.9% ± 6.2%; all were within the normal range. The mean LV global longitudinal strain (LVGLS) was -19.2% ± -1.9%; 6 patients had LVGLS